STRATEGY OF THE TASIKMALAYA CITY ENVIRONMENTAL OFFICE IN HANDLING HOUSEHOLD WASTE IN CIPEDES SUBDISTRICT: Array - Yunia Puspa Gustiani; Dini Yuliani (Faculty of Social And Political Science Universitas Galuh, 2021)
Research on the Strategy of the Tasikmalaya City Environmental Office in Handling Household Waste in Cipedes Subdistrict is motivated by the availability of waste transportation facilities and infrastructure that is still inadequate, lack of socialization on restrictions on the use of disposable packaging to the community, lack of human resources in waste transportation services. The research method used is a descriptive research method of analysis, with a qualitative approach. The data source in this study is 4 informants. Data collection techniques through interviews, observations, and documentation. Research data analysis techniques are data reduction, data presentation, and conclusion/verification withdrawal. Based on the results of the study that the Strategy of the Tasikmalaya City Environment Office in handling household waste in Cipedes Subdistrict has not been implemented optimally. The obstacles faced are in Human Resources (HR) and the lack of budget for the provision of waste facilities and infrastructure. Similarly, the budget becomes an obstacle in the socialization program on restrictions on the use of disposable packaging and development programs or training on the utilization of used goods. Efforts are made to coordinate with the village, and sub-district to empower the community in managing waste, as well as coordinating with producers to reduce plastic waste that is difficult to recycle.